METHOD FOR THE QUANTITATIVE ESTIMATION OF ESTRONE USING ANTIMONY TRICHLORIDE - FIERRO DEL RIO, LEONEL; AUPART ARRIETA, DELFINA (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1966)
The histological characteristics of the pinealomas are described as they appear after silver impregnation The lack of specific nervous extensions to the tumors and the formation of an alveolar pre-collagenous network are confirmed
MEX AGRI
Keywords: METHOD, QUANTITATIVE ESTIMATION, ESTRONE, ANTIMONY TRICHLORIDE; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL